1981
DOI: 10.1007/bf00253168
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies of the renal radiopharmaceutical compound dimercaptosuccinate

Abstract: Subcellular distribution of 99mTc-DMS (dimercaptosuccinic acid) complex in the rat kidney has been studied. One hour after IV injection of labelled DMS preparation kidney tissue homogenate was subjected to differential subfractionation to obtain cell organelles. Radioactivity distribution in relation to total radioactivity of kidney homogenate obtained in five repeated experiments was as follows (+/- SD): nuclei 4.56% (+/- 0.7); mitochondria 5.97% (+/- 0.7); microsomes 3.63% (+/- 0.8) and cytosol 30.92% (+/- 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…One hour after intravenous injection of labeled DMSA, kidney tissue homogenate preparations were subjected to differential subfractionation to obtain cell organelles. Radioactivity distribution in relation to total radioactivity of kidney homogenate obtained in five repeated experiments was similar to our results [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One hour after intravenous injection of labeled DMSA, kidney tissue homogenate preparations were subjected to differential subfractionation to obtain cell organelles. Radioactivity distribution in relation to total radioactivity of kidney homogenate obtained in five repeated experiments was similar to our results [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Other radiopharmaceuticals, such as 99m Tc-methoxyisobutylisonitrile (MIBI) and 99m Tc-dimercaptosuccinic acid (DMSA), have had their binding sites studied before [ 27 , 28 , 37 ]. Similar to our results, data from whole heart preparations, largely derived from differential centrifugation techniques, indicated that most of 99m Tc-MIBI appears to be associated with the cytosolic fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Tracer uptaken by these cells is reportedly bound to cytoplasmic proteins; this binding is important for retaining the compound intracellularly [19]. Our findings suggest that, in ITP, the depletion of these binding sites leads to the diffusion of 99m Tc-DMSA out of the cells.…”
Section: Discussionmentioning
confidence: 76%